2019
DOI: 10.1038/s41598-018-37734-w
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular-Subventricular Zone Contact by Glioblastoma is Not Associated with Molecular Signatures in Bulk Tumor Data

Abstract: Whether patients with glioblastoma that contacts the ventricular-subventricular zone stem cell niche (VSVZ + GBM) have a distinct survival profile from VSVZ − GBM patients independent of other known predictors or molecular profiles is unclear. Using multivariate Cox analysis to adjust survival for widely-accepted predictors, hazard ratios (HRs) for overall (OS) and progression free (PFS) survival between VSVZ + GBM and VSVZ − GBM patients were calculated in 170 single-institution patients and 254 patients incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 51 publications
3
19
0
Order By: Relevance
“…Using the same dataset however and our clinician-friendly definition of SVZ contact based on the enhancing tumor core rather than a complex image analysis algorithm, we did not find any association between molecular subtype and SVZ contact in this same TCGA/TCIA and our cohorts. Our results are in line with a recent report of similar analyses to explore this hypothesis with the TCGA/TCIA dataset [46].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Using the same dataset however and our clinician-friendly definition of SVZ contact based on the enhancing tumor core rather than a complex image analysis algorithm, we did not find any association between molecular subtype and SVZ contact in this same TCGA/TCIA and our cohorts. Our results are in line with a recent report of similar analyses to explore this hypothesis with the TCGA/TCIA dataset [46].…”
Section: Discussionsupporting
confidence: 93%
“…In a large institutional cohort (n = 647) and a cohort from the TCIA/TCGA repository (n = 222), we show that contact between the gadolinium-enhancing, T1-weighted imaging core component of glioblastomas and the SVZ of the brain is an adverse prognostic factor, independent of other known prognostic factors age, preoperative KPS, surgery type and postoperative treatment [37]. These results considerably strengthen the associations found by others, who had explored this hypothesis with univariable survival models [14, 16, 17, 3840] or smaller to mid-size cohorts [17, 18, 4146], and may help define the prognosis of individual patients based on their preoperative MR imaging. A meta-analysis of these published series also showed a significant adverse prognostic effect of SVZ contact in glioblastoma patients [47], but these analyses were not corrected for the effects of other (clinical) factors, due to unavailable individual patient data.…”
Section: Discussionsupporting
confidence: 64%
“…This finding mirrors the results of a prior study in GBMs that reported that SVZ involvement, though associated with decreased survival in GBMs, did not have a distinct molecular signature. 30 This prior study assessed tumor mutations, DNA methylation, gene expression, and protein expression, which suggests that SVZ involvement and molecular alterations may be independent prognostic factors. Among LGGs, SVZ involvement by oligodendrogliomas was previously reported to be associated with a mutation in the Capicua transcriptional repressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastomas with and without VSVZ invasion or contact are not genomically distinct in bulk profiling (9,10). Therefore, the more severe clinical phenotype of those patients is likely due t o t h e m i c r o e n v i r o n m e n t o f t h e V S V Z ( 9 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastomas with and without VSVZ invasion or contact are not genomically distinct in bulk profiling (9,10). Therefore, the more severe clinical phenotype of those patients is likely due t o t h e m i c r o e n v i r o n m e n t o f t h e V S V Z ( 9 ) . T h e microenvironment is especially attractive to glioblastoma cells (11,12), and factors released by the VSVZ can mediate resistance to radiation therapy in glioblastoma cells (13).…”
Section: Introductionmentioning
confidence: 99%